IMPLEMENTASI KEBIJAKAN SMART CITY DALAM MEWUJUDKAN KUALITAS PELAYANAN PUBLIK DI KOTA TANGERANG - Syamsul Bahri; Khasan Effendy; Ngadisah; Sampara Lukman (GoAcademica Research dan Publishing, 2020)
The problems that arise in this research are related to the implementation of policy policies in realizing quality public services in in Tangerang City which focuses on the use of information and communication technology via the internet, online, digital and social media. The research method used is descriptive method with a qualitative approach. The results showed that the implementation of the smart city policy in realizing quality public services in Tangerang City could not be implemented effectively in improving the welfare of the community in fact from the factors that influence including; (1) communication that affects all existing indicators, and skills indicators are still not effective; (2) Relevant resources from all the existing indicators, and lack of effective skills in the provision of facilities and infrastructure needed; (3) The related disposition of all the existing indicators, and the less effective level of trust taken by the leadership; (4) Bureaucratic structures related to all existing indicators, and which are still less effective and instructive according to the Standard Operating Procedure (SOP).